Heterogeneous Influence of Frailty Phenotypes in Age-Related Hearing Loss and Tinnitus in Chinese Older Adults: An Explorative Study - Ruan, Qingwei; Chen, Jie; Zhang, Ruxin; Zhang, Weibin; Ruan, Jian; Zhang, Min; Han, Chao; Yu, Zhuowei (Frontiers in Psychology, 2021)
Background: Fried physical frailty, with mobility frailty and non-motor frailty phenotypes, is a heterogeneous syndrome. The coexistence of the two phenotypes and cognitive impairment is referred to as cognitive frailty (CF). It remains unknown whether frailty phenotype has a different association with hearing loss (HL) and tinnitus. Methods: Of the 5,328 community-dwelling older adults, 429 participants aged ≥58 years were enrolled in the study. Participants were divided into robust, mobility and non-mobility frailty, mobility and non-mobility CF (subdivided into reversible and potential reversible CF, RCF and PRCF), cognitive decline (subdivided into mild cognitive impairment (MCI) and pre-MCI) stratifications. The severity of HL and tinnitus, and presented HL and/or tinnitus were used as dependent variable in multivariate logistic or nominal regression analyses with forward elimination adjusted for frailty phenotype stratifications and other covariates. Results: Patients with physical frailty (mobility frailty) or who are robust were found to have lower probability of developing severe HL and tinnitus, and presented HL and/or tinnitus than those with only cognitive decline, or CF. Patients with RCF and non-mobility RCF had higher probability with less HL and tinnitus, and the presentation of HL and/or tinnitus than those with PRCF and mobility RCF. Other confounders, age, cognitive and social function, cardiovascular disease, depression and body mass index, independently mediated the severity of HL and tinnitus, and presented HL and/or tinnitus. Conclusion: Frailty phenotypes have divergent association with HL and tinnitus. Further research is required to understand the differential mechanisms and the personalized intervention of HL and tinnitus.